PENGARUH KUALITAS INFORMASI, KUALITAS SISTEM DAN KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA - Syahra Syahra; Alida Palilati; Hayat Yusuf (Pascasarjana Universitas Halu Oleo, 2020)
This study aims to determine and analyze the effect of information quality, system quality and service quality on student satisfaction at the Faculty of Economics and Islamic Business, Muhammadiyah University, Kendari.The population in this study were FEBI UMK students totaling 510 people consisting of 2016 batch totaling 237 people and 2017 batch totaling 273 students. With 120 respondents. Hypothesis testing is done using SEM (Structural Equation Modeling) or Structural Equation Model with AMOS 4 program. The results showed that: Information quality has a significant effect on student satisfaction. The quality of the system has a negative and significant effect on student satisfaction. And Service Quality has a positive and significant effect on student satisfaction